Treatment outcomes of drug resistant tuberculosis patients with multiple poor prognostic indicators in Uganda: A countrywide 5-year retrospective study - Baluku, Joseph Baruch; Nakazibwe, Bridget; Naloka, Joshua; Nabwana, Martin; Mwanja, Sarah; Mulwana, Rose; Sempiira, Mike; Nassozi, Sylvia; Babirye, Febronius; Namugenyi, Carol; Ntambi, Samuel; Namiiro, Sharon; et al. (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2021)
Comorbid conditions and adverse drug events are associated with poor treatment outcomes among patients with drug resistant tuberculosis (DR – TB). This study aimed at determining the treatment outcomes of DR – TB patients with poor prognostic indicators in Uganda. We reviewed treatment records of DR – TB patients from 16 treatment sites in Uganda. Eligible patients had confirmed DR – TB, a treatment outcome in 2014–2019 and at least one of 15 pre-defined poor prognostic indicators at treatment initiation or during therapy. The pre-defined poor prognostic indicators were HIV co-infection, diabetes, heart failure, malignancy, psychiatric illness/symptoms, severe anaemia, alcohol use, cigarette smoking, low body mass index, elevated creatinine, hepatic dysfunction, hearing loss, resistance to fluoroquinolones and/or second-line aminoglycosides, previous exposure to second-line drugs (SLDs), and pregnancy. Tuberculosis treatment outcomes were treatment success, mortality, loss to follow up, and treatment failure as defined by the World Health Organisation. We used logistic and cox proportional hazards regression analysis to determine predictors of treatment success and mortality, respectively. Of 1122 DR – TB patients, 709 (63.2%) were male and the median (interquartile range, IQR) age was 36.0 (28.0–45.0) years. A total of 925 (82.4%) had ≥2 poor prognostic indicators. Treatment success and mortality occurred among 806 (71.8%) and 207 (18.4%) patients whereas treatment loss-to-follow-up and failure were observed among 96 (8.6%) and 13 (1.2%) patients, respectively. Mild (OR: 0.57, 95% CI 0.39–0.84, p = 0.004), moderate (OR: 0.18, 95% CI 0.12–0.26, p < 0.001) and severe anaemia (OR: 0.09, 95% CI 0.05–0.17, p < 0.001) and previous exposure to SLDs (OR: 0.19, 95% CI 0.08–0.48, p < 0.001) predicted lower odds of treatment success while the number of poor prognostic indicators (HR: 1.62, 95% CI 1.30–2.01, p < 0.001), for every additional poor prognostic indicator) predicted mortality. Among DR – TB patients with multiple poor prognostic indicators, mortality was the most frequent unsuccessful outcomes. Every additional poor prognostic indicator increased the risk of mortality while anaemia and previous exposure to SLDs were associated with lower odds of treatment success. The management of anaemia among DR – TB patients needs to be evaluated by prospective studies. DR – TB programs should also optimise DR – TB treatment the first time it is initiated.
Keywords: Drug resistant; Tuberculosis; Poor prognostic indicators